Biogeography of mycorrhizal symbiosis - Tedersoo, Leho (Springer, 2017)
This book offers a timely overview and synthesis of biogeographic patterns of plants and fungi and their mycorrhizal associations across geographic scales. Written by leading experts in the field, it provides an updated definition of mycorrhizal types and establishes the best practices of modern biogeographic analyses. Individual chapters address the basic processes and mechanisms driving community ecology, population biology and dispersal in mycorrhizal fungi, which differ greatly from these of prokaryotes, plants and animals. Other chapters review the state-of-the-art knowledge about the distribution, ecology and biogeography of all mycorrhizal types and the most important fungal groups involved in mycorrhizal symbiosis. The book argues that molecular methods have revolutionized our understanding of the ecology and biogeography of mycorrhizal symbiosis and that rapidly evolving high-throughput identification and genomics tools will provide unprecedented information about the structure and functioning of mycorrhizal symbiosis on a global scale. This volume appeals to scientists in the fields of plant and fungal ecology and biogeography.
Includes index.
Keywords: Mycorrhizas.; elektronické knihy; electronic books